From Classroom to Carbon Reduction: A Study of Maritime Cadet Awareness, Engagement, and Career Interest in Decarbonization and Green Shipping Initiatives Aligned with IMO 2050 Targets (International Journal of Economics Management and Social Science, 2026)
The maritime industry faces mandated decarbonization targets (International Maritime Organization 2050 carbon neutrality goals), yet maritime education curricula rarely address sustainability comprehensively, and cadets demonstrate limited awareness of green shipping opportunities. This mixed-methods study examined 412 maritime cadets from Indonesian maritime academies regarding their environmental awareness, understanding of decarbonization technologies and strategies, and career interest in green shipping positions. Qualitative interviews with 58 cadets, educators, and shipping company sustainability managers identified that while 73% of cadets express general environmental concern, only 19% could articulate specific IMO 2050 decarbonization strategies, and only 31% viewed sustainability careers as attractive professional pathways. Current maritime curricula address sustainability minimally; only 28% of respondents reported sustainability content in their programs, typically limited to regulatory compliance topics rather than strategic decarbonization. Quantitative survey analysis (Cronbach's α=0.78) revealed significant positive correlations between maritime educators' own environmental commitment and cadet engagement with sustainability topics (r=0.64, p